Binder resin for toner, toner for developing electrostatic image, and developer for electrostatic image

The introduction of a block copolymer binder resin with specific acid value ranges and aromatic ring structures addresses the poor emulsification and charging stability issues in existing binder resins, resulting in improved low-temperature fixing and charging performance.

JP7647082B2Active Publication Date: 2025-03-18DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020204859
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-10
Publication Date
2025-03-18
Estimated Expiration
2040-12-10

AI Technical Summary

Technical Problem

The binder resin disclosed in Patent Document 1 has poor emulsification properties due to low acid values of both crystalline and amorphous polyester blocks, leading to reduced charging stability and image defects.

Method used

A block copolymer binder resin with crystalline and amorphous polyester blocks having acid values within a specific range (4.0 to 16.0) and connected by a structure containing an aromatic ring, enhancing emulsification and charging performance.

Benefits of technology

The proposed binder resin achieves excellent low-temperature fixing and charging performance, maintaining emulsification properties and providing high charging stability to toner particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647082000001
    Figure 0007647082000001
  • Figure 0007647082000002
    Figure 0007647082000002
  • Figure 0007647082000003
    Figure 0007647082000003
Patent Text Reader

Abstract

To provide a toner binding resin capable of heightening low temperature fixability and chargeability of a toner.SOLUTION: A toner binder resin which is a block copolymer having a crystalline polyester block and an amorphous polyester block, in which an acid value of the crystalline polyester block is in the range of 4.0 to 16.0, and the acid value of the amorphous polyester block is in the range of 4.0 to 16.0, and has a structure represented by the following formula (1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder resin for a toner, a toner for developing an electrostatic image, and an electrostatic image developer. [Background technology]

[0002] In an image forming method involving the formation of an electrostatic latent image (electrostatic image), a two-component developer (toner) is usually used, which contains toner particles including a binder resin and a colorant, and carrier particles for stirring and transporting the toner particles. In the above image forming methods, there is a demand for a reduction in the thermal energy required for fixing toner particles (low-temperature fixing) in order to increase the speed of image formation and reduce the burden on the environment.

[0003] As a means for fixing toner particles at low temperatures, the use of a binder resin having both a crystalline resin portion and an amorphous resin portion at the same time has been proposed. In a binder resin having both a crystalline resin portion and an amorphous resin portion, when the melting point of the crystalline resin portion is exceeded by heating during fixing, the crystalline resin portion in the binder resin melts, and as a result, the crystalline resin portion and the amorphous resin portion become compatible with each other, thereby realizing low-temperature fixing of toner particles.

[0004] A block copolymer in which a crystalline polyester block and an amorphous polyester block are chemically bonded has been proposed as a binder resin for toner particles with improved low-temperature fixability (Patent Document 1). By using a block copolymer in which a crystalline polyester block and an amorphous polyester block are bonded, the compatibility between the crystalline polyester and the amorphous polyester is improved, and the toner particles can be finely dispersed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-92642 A Summary of the Invention [Problem to be solved by the invention]

[0006] The binder resin disclosed in Patent Document 1 has a problem that the acid value of both the crystalline polyester block and the amorphous polyester block is low, which reduces the emulsifiability of the binder resin, and in particular reduces the charging stability. A binder resin with reduced charging stability may cause image defects.

[0007] The problem to be solved by the present invention is to provide a binder resin for toner which is excellent in both low-temperature fixing property and charging performance. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result have found that the above-mentioned problems can be solved by a block copolymer in which a crystalline polyester block and an amorphous polyester block each have an acid value within a specific range and these polyester blocks are linked through a specific structure containing an aromatic ring, and have completed the present invention.

[0009] That is, the present invention relates to a toner binder resin which is a block copolymer having a crystalline polyester block and an amorphous polyester block, the crystalline polyester block having an acid value in the range of 4.0 to 16.0, the amorphous polyester block having an acid value in the range of 4.0 to 16.0, and the toner binder resin having a structure represented by the following formula (1):

[0010] [ka] (In the above formula (1), Ar is an aromatic ring; U 1 and U 2 One of the blocks is the crystalline polyester block, and the other is the amorphous polyester block. Effect of the Invention

[0011] The present invention can provide a binder resin for toner that is excellent in both low-temperature fixing property and charging performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the present invention will be described below. The present invention is not limited to the following embodiment, and can be implemented by making appropriate modifications within the scope that does not impair the effects of the present invention. In this application, when the expression "range of XX to □□" is used, it means greater than or equal to XX and less than or equal to □□.

[0013] [Binding resin for toner] The binder resin for toner of the present invention (hereinafter, may be simply referred to as "the binder resin of the present invention") is a block copolymer having a crystalline polyester block and an amorphous polyester block, the acid value of the crystalline polyester block being in the range of 4.0 to 16.0, the acid value of the amorphous polyester block being in the range of 4.0 to 16.0, and having a structure represented by the following formula (1).

[0014] [ka] (In the above formula (1), Ar is an aromatic ring; U 1 and U 2 One of the blocks is the crystalline polyester block, and the other is the amorphous polyester block.

[0015] The binder resin of the present invention has a structure in which an aromatic tetracarboxylic acid derivative forms ester bonds with a crystalline polyester and an amorphous polyester, and the crystalline polyester block and the amorphous polyester block each have an acid value within a specific range. In the present invention, it is presumed that, since the crystalline polyester block and the amorphous polyester block each have an acid value within a specific range, the end of the polyester block (which does not form an ester bond with the aromatic tetracarboxylic acid derivative) is a carboxyl group, and therefore reactions between the binder resins, etc. are suppressed and emulsifiability is maintained. The charging performance of toner particles is not only dependent on the charge amount, but also on the charge stability, which does not change over time. The binder resin of the present invention, which maintains its emulsifiability, can provide toner particles with high charge stability.

[0016] The binder resin of the present invention preferably has a high symmetry in the structure of the portion excluding the crystalline polyester block and the amorphous polyester block, and 1 and U 2 It is more preferable that the structure of the portion excluding the above is linearly symmetric or point symmetric.

[0017] The weight average molecular weight (Mw) of the binder resin of the present invention is, for example, in the range of 5,000 to 100,000, preferably in the range of 10,000 to 50,000, more preferably in the range of 15,000 to 50,000, and further preferably in the range of 15,000 to 45,000. The number average molecular weight (Mn) of the binder resin of the present invention is, for example, in the range of 1,000 to 50,000, preferably in the range of 2,000 to 30,000, more preferably in the range of 3,000 to 20,000, and further preferably in the range of 3,000 to 15,000. The weight average molecular weight and number average molecular weight of the binder resin of the present invention are measured by the method described in the Examples.

[0018] The binder resin of the present invention is a copolymer obtained by reacting a crystalline polyester resin having an acid value in the range of 4.0 to 16.0, an amorphous polyester resin having an acid value in the range of 4.0 to 16.0, and an aromatic tetracarboxylic acid derivative as reaction raw materials, and the aromatic tetracarboxylic acid derivative functions as a blocking agent that links the crystalline polyester resin and the amorphous polyester resin. The reactive raw materials refer to raw materials that constitute the binder resin of the present invention, and do not include solvents or catalysts that do not constitute the binder resin of the present invention.

[0019] In the formula (1), U 1 and U 2 The portion excluding the above corresponds to an aromatic tetracarboxylic acid derivative, and U 1 and U 2 are structures corresponding to a crystalline polyester resin and an amorphous polyester resin, respectively. Each component constituting the binder resin of the present invention will be described below.

[0020] (Crystalline polyester resin) The crystalline polyester resin is a crystalline polyester resin. Here, "crystalline" means that the polyester resin does not show a stepwise change in endothermic heat amount in differential scanning calorimetry (DSC), but shows a clear endothermic peak. Specifically, when the differential scanning calorimetry described in the examples is performed, the polyester resin that shows a clear endothermic peak is a crystalline polyester resin.

[0021] The acid value of the crystalline polyester resin is in the range of 4.0 to 16.0, preferably in the range of 5.0 to 15.0, and more preferably in the range of 8.1 to 15.0. In order to maintain the emulsifiability of the block copolymer, it is more preferable that the lower limit of the acid value of the crystalline polyester resin is more than 10.0. The acid value of the crystalline polyester resin is measured by the method described in the examples.

[0022] The melting point of the crystalline polyester resin is preferably 55 to 90°C, more preferably 61 to 88°C, and further preferably 64 to 85°C. The melting point of the crystalline polyester resin is measured by the method described in the examples.

[0023] The weight average molecular weight (Mw) of the crystalline polyester resin is, for example, in the range of 5,000 to 100,000, preferably in the range of 10,000 to 60,000, more preferably in the range of 15,000 to 40,000, and further preferably in the range of 19,000 to 39,000. The number average molecular weight (Mn) of the crystalline polyester resin is, for example, in the range of 1,000 to 50,000, preferably in the range of 2,000 to 10,000, more preferably in the range of 3,000 to 10,000, and further preferably in the range of 4,000 to 9,900. The weight average molecular weight and number average molecular weight of the crystalline polyester are measured by the method described in the examples.

[0024] Examples of the crystalline polyester resin include crystalline polyester resins obtained from an aliphatic dibasic acid (c1) and an aliphatic diol (c2) as essential reaction raw materials. Polyester resins are usually obtained as amorphous polyester resins, but crystalline polyester resins can be obtained by using a combination of an aliphatic dibasic acid (c1) and an aliphatic diol (c2) as reaction raw materials. It is more preferable that both the aliphatic dibasic acid (c1) and the aliphatic diol (c2) are highly symmetric and / or have a long hydrocarbon chain.

[0025] Examples of the aliphatic dibasic acid (c1) include aliphatic dibasic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, and nonyldecanedioic acid. Among these, aliphatic dibasic acids having 6 to 18 carbon atoms are preferred, and adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, and octadecanedioic acid are more preferred. These aliphatic dibasic acids may be used alone or in combination of two or more.

[0026] Examples of the aliphatic diol (c2) include linear alkylene diols such as ethylene glycol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, and 1,20-icosanediol; polyoxyethylene glycol, ... ether glycols such as dipropylene glycol; modified polyether polyols obtained by ring-opening polymerization of the above-mentioned linear alkylene diols with various cyclic ether bond-containing compounds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether; and lactone-based polyester polyols obtained by polycondensation reaction of the above-mentioned linear alkylene diols with various lactones such as ε-caprolactone. These aliphatic diols (c2) may be used alone or in combination of two or more.

[0027] The aliphatic diol (c2) is preferably a linear alkylene diol having 4 to 18 carbon atoms, more preferably 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, or 1,18-octadecanediol. All of these are highly symmetric aliphatic diols.

[0028] The crystalline polyester resin may use a polyfunctional epoxy compound (c3) as a reaction raw material. Examples of the polyfunctional epoxy compound (c3) include aliphatic diglycidyl ethers such as ethylene glycol diglycidyl ether, 2,2'-(2,6-dioxaheptane-1,7-diyl)bisoxirane, 1,4-bis(glycidyloxy)butane, 2,3-butylene glycol diglycidyl ether, 1,5-pentylene glycol diglycidyl ether, 1,6-bis(glycidyloxy)hexane, 1,7-heptylene glycol diglycidyl ether, and 1,8-octylene glycol diglycidyl ether; trimethylol Aliphatic polyglycidyl ethers having three or more epoxy groups in the molecular structure, such as diglycidylpropane triglycidyl ether and pentaerythritol tetraglycidyl ether; epoxy group-containing vinyl polymers obtained by polymerizing glycidyl group-containing compounds, such as glycidyl (meth)acrylate and α-ethyl (meth)acrylate, with vinyl group-containing aliphatic compounds, such as butadiene, methyl (meth)acrylate, ethyl (meth)acrylate, and dimethyl fumarate; bisphenol A diglycidyl ether, bisphenol B diglycidyl ether, aromatic diglycidyl ethers such as bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, 1,4-naphthalenediol diglycidyl ether, 1,5-naphthalenediol diglycidyl ether, 2,6-naphthalenediol diglycidyl ether, and naphthalene-2,6-dimethanol diglycidyl ether; aromatic polyglycidyl ethers having three or more epoxy groups in the molecular structure such as 4,4',4''-methylidynetrisphenol triglycidyl ether; novolac type epoxy resins such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, and bisphenol novolac type epoxy resins; and vinyl polymers containing an epoxy group and an aromatic ring obtained by polymerizing a glycidyl group-containing compound such as glycidyl (meth)acrylate or α-ethyl glycidyl (meth)acrylate with an aromatic compound containing a vinyl group such as styrene, and, if necessary, an aliphatic compound containing a vinyl group such as butadiene, methyl (meth)acrylate, ethyl (meth)acrylate, or dimethyl fumarate. Of these, novolac type epoxy resins are preferred. These polyfunctional epoxy compounds (c3) may be used alone or in combination of two or more.

[0029] The crystalline polyester resin may use, as a reaction raw material, an aliphatic monocarboxylic acid such as methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, heptadecanoic acid, or octadecanoic acid; or an aromatic dicarboxylic acid such as phthalic acid, phthalic anhydride, terephthalic acid, isophthalic acid, or orthophthalic acid, as necessary. These acid components other than the aliphatic dibasic acid (c1) may be used alone or in combination of two or more. By using an acid component other than the aliphatic dibasic acid (c1), the melting point of the crystalline polyester resin can be adjusted.

[0030] The crystalline polyester resin may use, as a reaction raw material, monoalcohols such as hexanol, octanol, n-decanol, n-undecanol, n-dodecanol, n-tridecanol, n-tetradecanol, n-pentadecanol, n-heptadecanol, n-octadecanol, n-nonadecanol, and eicosanol; aliphatic polyols having three or more functional groups such as trimethylolethane, trimethylolpropane, 2,2,4-trimethyl-1,3-pentanediol, glycerin, hexanetriol, and pentaerythritol; bisphenols such as bisphenol A, bisphenol B, bisphenol F, and bisphenol S; and alkylene oxide adducts of bisphenols obtained by adding ethylene oxide, propylene oxide, or the like to the above bisphenols. These alcohol components other than the aliphatic diol (c2) may be used alone or in combination of two or more. By using an alcohol component other than the aliphatic diol (c2), the melting point of the crystalline polyester resin can be adjusted.

[0031] The crystalline polyester resin may contain a monoepoxy compound as a reaction raw material, if necessary. Examples of the monoepoxy compound include aliphatic monoglycidyl ethers such as butyl glycidyl ether, 2-ethoxyethyl glycidyl ether, pentyl glycidyl ether, hexyl glycidyl ether, heptyl glycidyl ether, octyl glycidyl ether, 2-ethylhexyl glycidyl ether, nonyl glycidyl ether, and decyl glycidyl ether; monoglycidyl ethers having an aromatic ring in the molecular structure such as phenyl glycidyl ether, cresyl glycidyl ether, 4-butylphenyl glycidyl ether, and glycidyl-2-naphthyl ether; aliphatic monoglycidyl esters such as cyclopropylmethyl 2,2-dimethylpropionate, neodecanoic acid glycidyl ester, and stearic acid glycidyl ester; and aromatic α-olefin oxides such as styrene oxide. These monoepoxy compounds may be used alone or in combination of two or more.

[0032] A crystalline polyester having an acid value in the range of 4.0 to 16.0 can be produced by adjusting the ratio of dibasic acid to diol.

[0033] In the case where the crystalline polyester resin is a crystalline polyester resin obtained by using an aliphatic dibasic acid (c1) and an aliphatic diol (c2) as essential reaction raw materials, the crystalline polyester resin has a molar number (N COOH ) and the number of moles of hydroxyl groups contained in the aliphatic diol (c1) (N OH ) and the ratio [(N COOH ) / (N OH The crystalline polyester resin is preferably a crystalline polyester resin obtained by reacting an aliphatic dibasic acid (c1) and an aliphatic diol (c2) so that the ratio (ratio of the monomer units to the total monomer units) falls within the range of 1.00 / 0.95 to 1.00 / 1.00 at a temperature of 180 to 260°C in the presence of an esterification catalyst such as dibutyltin oxide.

[0034] (Amorphous polyester resin) The amorphous polyester resin is a polyester resin that is non-crystalline. Here, "amorphous" means that it does not show a clear endothermic peak in differential scanning calorimetry (DSC). Specifically, when the differential scanning calorimetry described in the examples is performed, the polyester resin that does not show a clear endothermic peak is an amorphous polyester resin.

[0035] The acid value of the amorphous polyester resin is in the range of 4.0 to 16.0, preferably in the range of 5.0 to 15.0, and more preferably in the range of 8.1 to 15.0. In order to maintain the emulsifiability of the block copolymer, it is more preferable that the lower limit of the acid value of the amorphous polyester is more than 10.0. The acid value of the amorphous polyester is measured by the method described in the examples.

[0036] Amorphous polyester resin has the property that in a low-temperature environment, it is in a glassy state with low molecular mobility and no fluidity, but as the temperature rises, its molecular mobility increases, its rigidity and viscosity decrease, and it becomes a rubbery state with increased fluidity. The temperature at which it transitions from the glassy state to the rubbery state is called the glass transition temperature (Tg). The glass transition temperature of the amorphous polyester resin is, for example, 45 to 100°C, preferably 50 to 90°C, more preferably 50 to 80°C, and further preferably 50 to 70°C. The glass transition temperature of the amorphous polyester resin is measured by the method described in the examples.

[0037] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, 3,000 to 150,000, preferably 4,000 to 80,000, more preferably 10,000 to 60,000, and further preferably 10,500 to 44,000. The number average molecular weight (Mn) of the amorphous polyester resin is, for example, 1,000 to 50,000, preferably 2,000 to 10,000, more preferably 2,500 to 8,000, and further preferably 2,500 to 6,000. The weight average molecular weight and number average molecular weight of the amorphous polyester are measured by the method described in the examples.

[0038] Examples of the amorphous polyester resin include amorphous polyester resins obtained by using a dibasic acid (a1) and a diol (a2) as essential reaction raw materials. The reaction raw materials for the amorphous polyester resin are preferably a combination of a dibasic acid and a diol other than the combination of an aliphatic dibasic acid (c1) and an aliphatic diol (c2) which are reaction raw materials for the crystalline polyester.

[0039] Examples of the dibasic acid (a1) include aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, hexahydrophthalic acid, 1,4-cyclohexanedicarboxylic acid, dodecylsuccinic acid, dodecylsuccinic anhydride, dodecenylsuccinic acid, dodecenylsuccinic anhydride, octenylsuccinic acid, and octenylsuccinic anhydride; aliphatic unsaturated dicarboxylic acids such as maleic acid, maleic anhydride, citraconic acid, dimethylmaleic acid, cyclopentene-1,2-dicarboxylic acid, 1-cyclohexene-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, fumaric acid, mesaconic acid, itaconic acid, and glutaconic acid; and aromatic dicarboxylic acids such as phthalic acid, phthalic anhydride, terephthalic acid, isophthalic acid, and orthophthalic acid. Of these, the aromatic dicarboxylic acids are preferred, with terephthalic acid and isophthalic acid being more preferred. These dibasic acids may be used alone or in combination of two or more.

[0040] Examples of the diol (a2) include aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propanediol, 1,2,2-trimethyl-1,3-propanediol, 2,2-dimethyl-3-isopropyl-1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, and 1,4-bis(hydroxymethyl)cyclohexane; ether glycols such as polyoxyethylene glycol and polyoxypropylene glycol; and mixtures of the above aliphatic diols with ethyleneoxy Examples of such polyols include modified polyether polyols obtained by ring-opening polymerization of various cyclic ether bond-containing compounds such as propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether; lactone-based polyester polyols obtained by polycondensation reaction of the above-mentioned aliphatic diols with various lactones such as ε-caprolactone; bisphenols such as bisphenol A, bisphenol B, bisphenol F, and bisphenol S; and alkylene oxide adducts of bisphenols obtained by adding ethylene oxide, propylene oxide, or the like to the above-mentioned bisphenols. Among these, the alkylene oxide adducts of bisphenols are preferred. These diols may be used alone or in combination of two or more.

[0041] The amorphous polyester resin may be prepared by using, as a reaction raw material, monocarboxylic acids such as methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, benzoic acid, and para-t-butylbenzoic acid; and polycarboxylic acids having three or more functional groups such as 1,2,5-hexanetricarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid, trimellitic acid, trimellitic anhydride, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, pyromellitic acid, and pyromellitic anhydride. These acid components other than the dibasic acid (a1) may be used alone or in combination of two or more. By using an acid component other than the dibasic acid (a1), the glass transition point of the amorphous polyester resin can be adjusted.

[0042] The amorphous polyester resin may be prepared, if necessary, using, as a reaction raw material, monoalcohols such as hexanol, 2-ethylhexanol, octanol, n-decanol, n-undecanol, n-dodecanol, n-tridecanol, n-tetradecanol, n-pentadecanol, n-heptadecanol, n-octadecanol, n-nonadecanol, eicosanol, 5-ethyl-2-nonanol, trimethylnonyl alcohol, 2-hexyldecanol, 3,9-diethyl-6-tridecanol, 2-isoheptylisoundecanol, 2-octyldodecanol, and 2-decyltetradecanol; or trifunctional or higher polyols such as trimethylolethane, trimethylolpropane, 2,2,4-trimethyl-1,3-pentanediol, glycerin, hexanetriol, and pentaerythritol. The alcohol component of the diol (a2) may be used alone or in combination of two or more. By using an alcohol component other than the diol (a2), the glass transition point of the amorphous polyester resin can be adjusted.

[0043] The amorphous polyester resin may use a polyfunctional epoxy compound as a reaction raw material, if necessary. The polyfunctional epoxy compound that can be used for the amorphous polyester resin may be the same as the polyfunctional epoxy compound (c3) that can be used for the crystalline polyester resin.

[0044] The amorphous polyester resin may contain a monoepoxy compound as a reaction raw material, if necessary. Examples of the monoepoxy compound include aliphatic monoglycidyl ethers such as butyl glycidyl ether, 2-ethoxyethyl glycidyl ether, pentyl glycidyl ether, hexyl glycidyl ether, heptyl glycidyl ether, octyl glycidyl ether, 2-ethylhexyl glycidyl ether, nonyl glycidyl ether, and decyl glycidyl ether; monoglycidyl ethers having an aromatic ring in the molecular structure such as phenyl glycidyl ether, cresyl glycidyl ether, 4-butylphenyl glycidyl ether, and glycidyl-2-naphthyl ether; aliphatic monoglycidyl esters such as cyclopropylmethyl 2,2-dimethylpropionate, neodecanoic acid glycidyl ester, and stearic acid glycidyl ester; and aromatic α-olefin oxides such as styrene oxide. These monoepoxy compounds may be used alone or in combination of two or more.

[0045] Amorphous polyesters having an acid value in the range of 4.0 to 16.0 can be produced by adjusting the ratio of dibasic acid to diol.

[0046] In the case where the amorphous polyester resin is an amorphous polyester resin obtained by using a dibasic acid (a1) and a diol (a2) as essential reaction raw materials, the amorphous polyester resin has a molar number (N COOH ) and the number of moles of hydroxyl groups contained in diol (a2) (N OH ) and the ratio [(N COOH ) / (N OHThe amorphous polyester resin is preferably a polyester resin obtained by reacting a dibasic acid (a1) and a diol (a2) so that the ratio (a1 / a2) of the dibasic acid (a1) and the diol (a2) falls within the range of 1.00 / 0.96 to 1.00 / 1.04 at a temperature of 180 to 260° C. in the presence of an esterification catalyst such as dibutyltin oxide.

[0047] (Aromatic tetracarboxylic acid derivatives) The aromatic ring of the aromatic tetracarboxylic acid derivative corresponds to Ar in the above formula (1). Examples of the aromatic ring of the aromatic tetracarboxylic acid derivative include a benzene ring, a naphthalene ring, and a structure in which two rings selected from these are linked by a single bond, an ether bond, an amide bond, or a carbonyl bond, and a benzene ring is preferred. The aromatic ring may be further substituted with an alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, or an n-pentyl group.

[0048] The aromatic tetracarboxylic acid derivative is preferably a compound in which all four carboxyl groups (-COOH) are directly substituted on an aromatic ring, due to its high reactivity with crystalline polyesters and amorphous polyesters, and is preferably an aromatic tetracarboxylic acid dianhydride. Examples of the aromatic tetracarboxylic dianhydride include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, and m-terphenyl-3,3',4,4'-tetracarboxylic dianhydride. , 4,4'-(2,2-hexafluoroisopropylene)diphthalic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)propanes, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, (1,1':3',1"-terphenyl)-3,3",4,4"-tetracarboxylic dianhydride, 4,4'-(dimethylsiladiyl)diphthalic dianhydride, and 4,4'-(1,4-phenylenebis(oxy))diphthalic dianhydride.

[0049] Regarding the structure represented by the formula (1), U 1 and U 2 When the structure of the portion excluding the above is line-symmetric or point-symmetric, a higher electric permittivity and higher crystallinity can be exhibited. Therefore, the aromatic tetracarboxylic acid derivative is preferably an aromatic tetracarboxylic acid derivative having a line-symmetric or point-symmetric structure.

[0050] [Method of manufacturing binder resin for toner] In the method for producing a binder resin of the present invention, a crystalline polyester resin having an acid value in the range of 4.0 to 16.0, a non-crystalline polyester resin having an acid value in the range of 4.0 to 16.0, and a reaction raw material essentially containing an aromatic tetracarboxylic acid derivative are reacted with each other.

[0051] The crystalline polyester resin, which is a reaction raw material, may be used alone or in combination of two or more kinds having different structures. The amorphous polyester resin, which is a reaction raw material, may be used alone or in combination of two or more types having different structures. The aromatic tetracarboxylic acid derivatives as the reaction raw materials may be used alone or in combination of two or more kinds having different structures.

[0052] The reaction temperature is, for example, 130°C or higher and lower than 200°C, preferably 140°C or higher and lower than 170°C, and more preferably 140°C or higher and 160°C or lower. When the aromatic tetracarboxylic acid derivative has a carboxylic anhydride structure, the reactivity with the polyester resin can be increased, and the derivative can react with the crystalline polyester resin and the amorphous polyester resin even at a temperature lower than 200° C. By producing the binder resin of the present invention at a temperature lower than 200° C., the crystallinity of the crystalline polyester resin is not impaired, and the low-temperature fixability of the binder resin obtained can be improved.

[0053] The reaction raw materials containing a crystalline polyester resin, an amorphous polyester resin, and an aromatic tetracarboxylic acid derivative may consist only of the crystalline polyester resin, the amorphous polyester resin, and the aromatic tetracarboxylic acid derivative, or may contain other reaction raw materials as desired.

[0054] The mass ratio of the crystalline polyester resin to the amorphous polyester resin used in producing the binder resin of the present invention is preferably crystalline polyester resin:amorphous polyester resin=20:80 to 80:20, more preferably crystalline polyester resin:amorphous polyester resin=25:75 to 75:25, and further preferably crystalline polyester resin:amorphous polyester resin=25:75 to 50:50.

[0055] The amount of the aromatic tetracarboxylic acid derivative used in the production of the binder resin of the present invention is, for example, 0.1 to 10 parts by mass, preferably 0.5 to 7 parts by mass, and more preferably 1 to 6 parts by mass, relative to 100 parts by mass of the total amount of the crystalline polyester resin and the amorphous polyester resin.

[0056] The reaction of the reaction raw materials including the crystalline polyester resin, the amorphous polyester resin, and the aromatic tetracarboxylic acid derivative can be carried out without a solvent because the reaction between the binder resins can be suppressed and the increase in viscosity can be suppressed. Since no solvent is required, the production cost can be reduced. The reaction is preferably carried out in an atmosphere of an inert gas such as argon or nitrogen while removing water produced in the reaction.

[0057] In the method for producing a binder resin of the present invention, not only a resin in which a crystalline polyester resin and an amorphous polyester resin are linked via an aromatic tetracarboxylic acid derivative, but also a resin in which two crystalline polyester resins are linked via an aromatic tetracarboxylic acid derivative, or a resin in which two amorphous polyester resins are linked via an aromatic tetracarboxylic acid derivative can be obtained, without impairing the effects of the present invention.

[0058] The structure of the resin obtained by the production method of the present invention can be confirmed or estimated by a known instrumental analysis method such as NMR or electrospray ionization mass spectrometry (ESI-MS) of the binder resin or a hydrolyzate thereof.

[0059] [Toner for developing electrostatic images] The toner for developing electrostatic images of the present invention contains the binder resin for toner of the present invention. The toner for developing electrostatic images of the present invention (hereinafter, may be simply referred to as "the toner of the present invention") is excellent in both low-temperature fixing property and charging performance by containing the binder resin of the present invention.

[0060] The content of the binder resin of the present invention in the toner of the present invention is not particularly limited, but is preferably 10 to 95 mass %, more preferably 25 to 90 mass %, and even more preferably 45 to 85 mass %, based on the total mass of the toner. When the content of the binder resin of the present invention is within the above range, excellent low-temperature fixability and charging performance can be obtained.

[0061] (Other binder resins) The toner of the present invention is only required to contain the binder resin of the present invention, and may contain a binder resin other than the binder resin of the present invention. The other binder resins are not particularly limited, and examples thereof include polystyrene, styrene-butadiene polymers, styrene-acrylic polymers, polyester resins, etc. These other binder resins may be further modified with urethane, urea, epoxy, etc.

[0062] The content of the binder resin of the present invention in the toner of the present invention is preferably from 20 to 100% by mass, and more preferably from 50 to 100% by mass, based on the total mass of the binder resin in the toner.

[0063] (Coloring agent) The toner of the present invention preferably contains a colorant for the purpose of coloring the resulting image. The colorant may be appropriately selected from known colorants depending on the purpose, and pigments and dyes of various colors may be used.

[0064] Examples of the pigments include black pigments such as carbon black, copper oxide, manganese dioxide, aniline black, activated carbon, non-magnetic ferrite, and magnetite; yellow pigments such as yellow lead, zinc yellow, yellow iron oxide, cadmium yellow, chrome yellow, Hansa Yellow, Hansa Yellow 10G, benzidine yellow G, benzidine yellow GR, threne yellow, quinoline yellow, and permanent yellow NCG; orange pigments such as red yellow lead, molybdenum orange, permanent orange GTR, pyrazolone orange, Balkan orange, benzidine orange G, induthrene brilliant orange RK, and induthrene brilliant orange GK; red iron oxide, cadmium red, red lead, mercury sulfide, watching red, permanent red 4R, lithol red, brilliant carmine 3B, brilliant Examples of suitable pigments include red pigments such as trimethylsiloxane 6B, pyrazolone red, rhodamine lake B, lake red C, rose bengal, eosin red, and alizarin lake; blue pigments such as iron blue, cobalt blue, alkali blue lake, Victoria blue lake, fast sky blue, indanthrene blue BC, ultramarine blue, phthalocyanine blue, and phthalocyanine green; purple pigments such as manganese purple, fast violet B, and methyl violet lake; green pigments such as chromium oxide, chrome green, pigment green B, malachite green lake, and fanal yellow green G; white pigments such as zinc oxide, titanium oxide, antimony white, and zinc sulfide; and extender pigments such as baryte powder, barium carbonate, clay, silica, white carbon, talc, and alumina white. These pigments may be used alone or in combination of two or more.

[0065] Examples of the dye include various dyes such as basic dyes, acid dyes, disperse dyes, and direct dyes. Specific examples of the dye include nigrosine, methylene blue, rose bengal, and quinoline yellow. These dyes may be used alone or in combination of two or more.

[0066] The colorant may be used, for example, in the form of a dispersion of colorant particles. Methods for preparing a dispersion of colorant particles include preparing a dispersion of colorant particles using a media-type dispersing machine such as a rotary shear homogenizer, a ball mill, a sand mill, or an attritor; or a high-pressure counter-impingement type dispersing machine, or preparing a dispersion of colorant particles using a homogenizer after adding a polar surfactant.

[0067] The content of the colorant in the toner of the present invention is preferably 0.1 to 40% by mass, more preferably 0.5 to 20% by mass, of the total mass of the solid content of the toner in order to ensure color development during fixing. However, when a magnetic material is used as the black colorant, the content of the black colorant is preferably 12 to 48% by mass, more preferably 15 to 40% by mass, of the total mass of the solid content of the toner.

[0068] By appropriately selecting the type of the colorant, toners of various colors such as yellow toner, magenta toner, cyan toner, black toner, etc. can be obtained.

[0069] (Release agent) The toner of the present invention preferably contains a release agent for the purpose of improving releasability. Examples of the release agent include low molecular weight polyolefins such as polyethylene, polypropylene, and polybutene; silicones that have a softening point when heated; fatty acid amides such as oleic acid amide, erucic acid amide, ricinoleic acid amide, and stearic acid amide; vegetable waxes such as carnauba wax, rice wax, candelilla wax, wood wax, and jojoba oil; animal waxes such as beeswax; mineral and petroleum waxes such as montan wax, ozokerite, ceresin, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax; and ester waxes such as fatty acid esters, montan acid esters, and carboxylic acid esters. These release agents may be used alone or in combination of two or more.

[0070] The amount of the release agent added is preferably 0.5 to 50% by mass, more preferably 1 to 30% by mass, and further preferably 5 to 15% by mass, based on the total amount of the toner particles.

[0071] The toner of the present invention may contain other components in addition to the binder resin, the colorant, and the release agent, as long as the effects of the present invention are not impaired. Examples of the other components include known additives such as inorganic particles, organic particles, internal additives, and charge control agents.

[0072] The inorganic particles are generally used for the purpose of improving the fluidity of the toner. Examples of the inorganic particles include particles of silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, cerium chloride, red iron oxide, chromium oxide, cerium oxide, antimony trioxide, magnesium oxide, zirconium oxide, silicon carbide, silicon nitride, etc. Among these, silica particles are preferred, and hydrophobically treated silica particles are particularly preferred.

[0073] The organic particles are used for the purpose of improving the cleaning property, transfer property, charge property, and the like. Examples of the organic particles include particles of polystyrene, polymethyl methacrylate, polyvinylidene fluoride, polystyrene-acrylic copolymer, and the like.

[0074] Examples of the internal additive include magnetic materials such as metals, alloys, and compounds containing these metals, such as ferrite, magnetite, reduced iron, cobalt, nickel, and manganese. Examples of the charge control agent include metal salicylate, metal-containing azo compounds, nigrosine, and quaternary ammonium salts.

[0075] The toner of the present invention can be produced by a known method, for example, a kneading and pulverizing method, an emulsion aggregation method, a suspension polymerization method, or a dissolution suspension method, and the emulsion aggregation method is preferred. The kneading and pulverizing method is a method for producing toner base particles by kneading a binder resin with a colorant, a release agent, a charge control agent, etc., and pulverizing and classifying the resulting kneaded product. The resulting toner base particles may be further subjected to a mechanical impact force or thermal energy to change the shape. The emulsion aggregation method is a method of producing toner base particles by mixing a dispersion liquid in which a binder resin is emulsified and dispersed with a dispersion liquid of a colorant, a release agent, a charge control agent, etc., and aggregating and heat fusing the mixture. The suspension polymerization method is a method for producing toner base particles by suspending a polymerizable monomer for obtaining a binder resin and solutions of a colorant, a release agent, a charge control agent, etc. in an aqueous solvent. The dissolution suspension method is a method in which a binder resin and solutions of a colorant, a release agent, a charge control agent, etc. are suspended in an aqueous solvent to form toner base particles. The toner base particles obtained by the above method may be used as a core, and aggregated particles may be attached to the surface of the core, followed by heating and fusing to form a toner having a core-shell structure.

[0076] [Electrostatic image developer] The toner of the present invention is suitably used as an electrostatic image developer. The electrostatic image developer of the present invention may contain the toner of the present invention. For example, when the toner of the present invention is used alone as the electrostatic image developer, the electrostatic image developer of the present invention becomes a one-component electrostatic image developer, and when the toner of the present invention is used in combination with a known carrier as the electrostatic image developer, the electrostatic image developer becomes a two-component electrostatic image developer.

[0077] Examples of the core material of the carrier include magnetic metals such as iron, steel, nickel, and cobalt; alloys of the magnetic metals with manganese, chromium, and rare earth elements; and magnetic oxides such as ferrite and magnetite.

[0078] The surface of the core material of the carrier may be coated with a resin. Examples of the resin that coats the surface of the core material include polyolefin resins such as polyethylene and polypropylene; polystyrene, acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; polyvinylidene resins; vinyl chloride-vinyl acetate copolymers; styrene-acrylic acid copolymers; straight silicone resins or modified products thereof that are made of organosiloxane bonds; fluorine-based resins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; silicone resins; polyesters; polyurethanes; polycarbonates; phenolic resins; amino resins such as urea-formaldehyde resins, melamine resins, benzoguanamine resins, urea resins, and polyamide resins; and epoxy resins. These resins may be used alone or in combination of two or more.

[0079] When the carrier is a carrier made of a core material coated with a resin, it is preferable that resin particles and / or conductive particles are dispersed in the resin coating layer. The resin particles include thermoplastic resin particles and thermosetting resin particles. The resin particles may be used alone or in combination of two or more kinds. Examples of the conductive particles include metal particles such as gold, silver, and copper, carbon black particles, and particles whose surfaces are covered with carbon black or metal, such as titanium oxide, zinc oxide, barium sulfate, aluminum borate, and potassium titanate. These conductive particles may be used alone or in combination of two or more kinds.

[0080] The toner or electrostatic image developer of the present invention is used in a state of being accommodated in, for example, a cartridge. By accommodating the toner or electrostatic image developer of the present invention in a cartridge, the cartridge becomes detachable from an image forming apparatus, and it is possible to easily supply the toner or electrostatic image developer to the image forming apparatus. EXAMPLES

[0081] The present invention will be specifically described below with reference to examples and comparative examples. However, the present invention is not limited to the following examples.

[0082] Various evaluations in the examples were carried out by the following methods.

[0083] (Acid value and hydroxyl value) The acid value and hydroxyl value of the resin were measured in accordance with JIS K0070-1992 (neutralization titration method).

[0084] (Number average molecular weight and weight average molecular weight) The number average molecular weight (Mn) and weight average molecular weight (Mw) of the resin were evaluated by gel permeation chromatography (GPC) under the following conditions. Measuring device: Tosoh Corporation HLC-8120GPC Column: TSK-GUARDCOLUMN HXL-H manufactured by Tosoh Corporation +Tosoh Corporation TSK-GEL G5000HXL +Tosoh Corporation TSK-GEL G4000HXL +Tosoh Corporation TSK-GEL G3000HXL +Tosoh Corporation TSK-GEL G2000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation Multistation GPC-8020modelII Column temperature: 40℃ Solvent: Tetrahydrofuran Flow rate: 1.0ml / min Standard: Monodisperse polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.5% by mass of resin solids filtered through a microfilter

[0085] (Melting Point) The melting point of the resin was determined by differential scanning calorimetry (DSC) under the following conditions. Measurement device: Seiko Instruments Inc. DSC-220C Data processing: EXSTAR6000 PC station Measurement conditions: (1) Heat from 20°C to 150°C (10°C / min) (2) Hold at 150°C for 10 minutes (3) Decrease temperature from 150°C to 0°C (10°C / min) (4) Hold at 0°C for 10 minutes (5) Heat from 0°C to 150°C (10°C / min) In analysis (5), the maximum endothermic peak temperature of the heat of fusion was taken as the melting point.

[0086] (glass transition temperature) The glass transition temperature of the resin was determined by differential scanning calorimetry (DSC) under the following conditions. Measurement device: Seiko Instruments Inc. DSC-220C Data processing: EXSTAR6000 PC station Measurement conditions: (1) Heat from 20°C to 150°C (10°C / min) (2) Hold at 150°C for 10 minutes (3) Decrease temperature from 150°C to 0°C (10°C / min) (4) Hold at 0°C for 10 minutes (5) Heat from 0°C to 150°C (10°C / min) Analysis: In (5), the glass transition point was determined as the intersection of an extension of the low-temperature baseline and a tangent drawn at the point where the gradient of the curve of the step-like change in the glass transition is maximum.

[0087] (Synthesis Example 1-8: Synthesis of crystalline polyester resin) The raw materials shown in Table 1 were charged into a four-necked 3 L stainless steel flask equipped with a stirrer, a nitrogen gas inlet, and a thermometer. After charging the raw materials, the temperature was raised to 220°C over 6 hours under a nitrogen stream while removing the generated water, and the reaction was continued at 220°C until the target acid value and molecular weight were reached, obtaining crystalline polyester resins C-1 to C-8. The acid value, hydroxyl value, number average molecular weight, weight average molecular weight and melting point of each of the obtained crystalline polyester resins C-1 to C-8 were evaluated. The results are shown in Table 1.

[0088] [Table 1]

[0089] In Table 1, the abbreviations for each component represent the following: EG: Ethylene glycol BG: 1,4-butanediol HD: 1,6-Hexanediol DDD: 1,12-dodecanediol SeA: Sebacic acid DDDA: Dodecanedioic acid

[0090] (Synthesis Examples 9 to 14: Synthesis of amorphous polyester resins) The raw materials shown in Table 3 were charged into a four-necked 3 L stainless steel flask equipped with a stirrer, a nitrogen gas inlet, and a thermometer, and 0.8 parts of titanium tetraisopropoxide was added as a catalyst. After the raw materials were charged, they were reacted at 240°C for 3 hours under a nitrogen stream while removing the generated water, and then further reacted at 220°C under a reduced pressure of 5 kPa until the target acid value and molecular weight were reached, to obtain amorphous polyester resins A-1 to A-6, respectively. The acid value, hydroxyl value, number average molecular weight, weight average molecular weight and glass transition point of each of the obtained amorphous polyester resins A-1 to A-6 were evaluated. The results are shown in Table 2. Incidentally, the obtained amorphous polyester resins A-1 to A-6 did not show a clear endothermic peak in differential scanning calorimetry.

[0091] [Table 2]

[0092] In Table 2, the abbreviations stand for the following: BPAEO: Bisphenol A ethylene oxide adduct BPAPO: Bisphenol A propylene oxide adduct TPA: Terephthalic acid TMAn: Trimellitic anhydride DSA: Dodecenyl succinic anhydride

[0093] (Examples 1 to 12: Synthesis of block copolymers B-1 to B-12) The crystalline polyester resins and amorphous polyester resins shown in Tables 3 and 4 were charged into a four-necked 1 L stainless steel flask equipped with a stirrer, a nitrogen gas inlet, and a thermometer, and were heated and melted at 150° C. The blocking agents shown in Tables 3 and 4 were added to the melts, and the mixture was reacted at 150° C. for 4 hours to obtain block copolymers B-1 to B-12 having crystalline polyester blocks and amorphous polyester blocks, respectively. The acid value, number average molecular weight, weight average molecular weight and melting point of the obtained block copolymer were evaluated. The results are shown in Tables 3 and 4.

[0094] [Table 3]

[0095] [Table 4]

[0096] In Tables 3 and 4, the abbreviations stand for the following: PMAn: Pyromellitic anhydride

[0097] (Comparative Examples 1 to 6: Synthesis of Block Copolymers B'-1 to B'-6) The crystalline polyester resin and amorphous polyester resin shown in Table 5 were charged into a four-necked 1 L stainless steel flask equipped with a stirrer, a nitrogen gas inlet, and a thermometer, and melted by heating at 150° C. The blocking agent shown in Table 5 was added to this melt, and the mixture was reacted at 150° C. for 4 hours to obtain block copolymers B'-1 to B'-6 having crystalline polyester blocks and amorphous polyester blocks, respectively. The acid value, number average molecular weight, weight average molecular weight and melting point of the obtained block copolymer were evaluated. The results are shown in Table 5.

[0098] [Table 5]

[0099] In Table 5, the abbreviations stand for the following: An1: 1,2,3,4-butanetetracarboxylic dianhydride An2: 1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride

[0100] [ka]

[0101] (Examples 13 to 24 and Comparative Examples 7 to 12: Toner Production) (Synthesis of Dispersing Resin) In a 4-necked 3L stainless steel flask equipped with a stirrer, nitrogen gas inlet, and thermometer, 281.7 parts by mass of bisphenol A ethylene oxide adduct, 828.6 parts by mass of bisphenol A propylene oxide adduct, 400.6 parts by mass of terephthalic acid, 72.4 parts by mass of adipic acid, 23.8 parts by mass of trimellitic anhydride, and 0.8 parts by mass of titanium tetraisopropoxide as a catalyst were added. After the raw materials were charged, the mixture was reacted at 240°C for 7 hours under a nitrogen stream while removing the generated water, to obtain a dispersion resin.

[0102] (Preparation of Pigment Dispersion) 200 parts by mass of Fastogen Blue TGR (β-type copper phthalocyanine pigment, CI Pigment Blue 15:3, manufactured by DIC Corporation) and 200 parts by mass of the dispersion resin were kneaded with a twin roll. The kneaded mixture and 740 parts by mass of methyl ethyl ketone were charged into a ball mill and stirred for 6 hours, and the solid content was adjusted to 20% by mass with methyl ethyl ketone to obtain a pigment dispersion.

[0103] (Preparation of release agent dispersion) 200 parts by mass of Carnauba wax No. 1 (melting point 83.1°C, vegetable wax manufactured by Kato Yoko Co., Ltd.) and 200 parts by mass of the dispersion resin were kneaded with a pressure kneader. The kneaded product obtained and 740 parts by mass of methyl ethyl ketone were charged into a ball mill and stirred for 6 hours, and the solid content was adjusted to 20% by mass with methyl ethyl ketone to obtain a release agent dispersion.

[0104] (Preparation of wet mixed mill base) Block copolymers B-1 to B-12 and block copolymers B'-1 to B'-6, the pigment dispersion, and the release agent dispersion were mixed in the amounts shown in Tables 6 to 8 using a Desper, and the resulting mixture was added with methyl ethyl ketone to adjust the solid content to 55 mass%, thereby obtaining millbases MB-1 to MB-12 and millbases MB'-1 to MB'-6.

[0105] (Toner manufacturing) In a 2L separable flask equipped with a Max Blending blade, 545.5 parts by mass of each of Mill Bases MB-1 to MB-12 and Mill Bases MB'-1 to MB'-6, and 23.8 parts by mass of 1N ammonia water were added, and the mixture was thoroughly stirred at 350 rpm using a Three-One motor, and the temperature was adjusted to 30°C, and 266 parts by mass of deionized water was added dropwise to cause phase inversion emulsification. After phase inversion emulsification, 333 parts by mass of deionized water was added to prepare a fine particle dispersion. Next, 4.1 parts by mass of a nonionic emulsifier, polyoxyethylene polyoxypropylene glycol (Epane 450, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), was added, and the rotation speed was adjusted to 250 rpm while maintaining the temperature at 30°C. 410 parts by mass of a 3% aqueous ammonium sulfate solution was added dropwise, and the mixture was stirred for 5 minutes to effect coalescence, thereby obtaining a slurry. The obtained slurry was subjected to solid-liquid separation using a centrifuge, washed, and dried in a vacuum dryer to obtain toner particles. Using a Henschel mixer, 0.5 parts by mass of hydrophobic silica (H-2018, manufactured by Clariant Co., Ltd.) and 0.5 parts by mass of titanium oxide (JMT-150AO, manufactured by Teika Co., Ltd.) were externally added to 100 parts by mass of the toner particles to obtain toners T-1 to T-12 and toners T'-1 to T'-6, respectively. The obtained toner was subjected to the following evaluations, and the results are shown in Tables 6 to 8.

[0106] (Low temperature fixability) The toner was loaded into a copier, and solid printing was performed with the heat roll temperature varied from 80°C to 140°C in 5°C increments. A fastness test was performed on the solid printed area, and the image density before and after the test was measured with a Macbeth densitometer (RD-918). The temperature at which the ratio of the density value after peeling to the value before the test was expressed as a percentage and reached 80% or higher was defined as the fixing start temperature. The lower this temperature, the better the low-temperature fixing ability. The evaluation criteria for the low temperature fixability of the toner were as follows: The fastness test was carried out using a Gakushin type friction fastness tester (load: 200 g, rubbing operation: 5 strokes). ◎: When the fixing start temperature is less than 110℃ ○: When the fixing start temperature is 110℃ or higher and less than 115℃ △: When the fixing start temperature is 115℃ or higher and less than 120℃ ×: When the fixing start temperature is 120°C or higher

[0107] (Heat-resistant storage stability) 66g / cm under 40℃ 50% RH 2 The toner sample was left for 48 hours under a load of 100 g. 400 g of this sample was vibrated for 30 seconds at an amplitude of 1 mm using a vibrating sieve device equipped with a sieve with 45 μm openings. The percentage of aggregates remaining on the sieve was evaluated according to the following criteria. The smaller the percentage of aggregates, the better the heat-resistant storage stability. ◎: Less than 10% by mass ○: Less than 10-20% by mass △: Less than 20-30% by mass ×: 30% by mass or more

[0108] (Charge amount and charge stability) Using a suction blow-off type charge measurement device (210HS-2A, manufactured by Trek Japan Co., Ltd.), a mixture of 1.5 g of toner and 48.5 g of ferrite carrier (MF-1008, manufactured by Nippon Iron Powder Co., Ltd.) was mixed in a 50 ml plastic container for 1 minute, 10 minutes, 30 minutes, and 60 minutes using a Turbula Shaker Mixer, and the charge amount of each of the resulting mixtures was measured using the charge measurement device. The average value of the measured charge amounts was taken as the charge amount of the toner. The evaluation criteria for the charge amount were as follows: ◎ :-45μC / g or more ○: -40μC / g or more and less than -45μC / g △: -35μC / g or more and less than -40μC / g × : -30μC / g or more and less than -35μC / g ××: Less than -30μC / g In addition, the difference between the maximum charge amount and the minimum charge amount was calculated for the charge amount of the mixture mixed for 10 minutes, 30 minutes, and 60 minutes, and this value was used to evaluate the charge stability. The smaller this value, the better the charge stability. The evaluation criteria for the charge stability were as follows. ◎: The difference between the maximum and minimum charge amounts is less than -3μC / g ○: The difference between the maximum charge amount and the minimum charge amount is -3μC / g or more and less than -6μC / g △: The difference between the maximum and minimum charge amounts is -6μC / g or more and less than -9μC / g ×: The difference between the maximum charge amount and the minimum charge amount is -9 μC / g or more and less than -12 μC / g

[0109] [Table 6]

[0110] [Table 7]

[0111] [Table 8]

[0112] As can be seen from the results of Tables 6 to 8, the toners containing the block copolymers of the present invention are excellent in both low-temperature fixability and chargeability. On the other hand, in Comparative Examples 7 to 10, the low acid value of the polyester block reduces the emulsification ability, impairing the low-temperature fixability and charge amount, in Comparative Example 11, the charge amount and charge stability are insufficient because the block copolymer does not contain an aromatic ring, and in Comparative Example 12, the blocking agent of the block copolymer does not substitute a carboxyl group for an aromatic ring, and the structural symmetry is insufficient, impairing the charge amount.

Claims

1. A toner binder resin which is a copolymer made by reacting a crystalline polyester resin, an amorphous polyester resin, and an aromatic tetracarboxylic acid derivative, The acid value of the crystalline polyester resin is in the range of 4.0 to 16.0, The acid value of the amorphous polyester resin is in the range of 4.0 to 16.0, A toner binder resin having a structure represented by the following formula (1): 【Chemistry 1】 (In the above formula (1), Ar is a structure obtained by removing four carboxyl groups from the aromatic tetracarboxylic acid derivative, U 1 and U 2 One of the blocks corresponds to the crystalline polyester resin, and the other corresponds to the amorphous polyester resin.

2. U in the formula (1) 1 and U 2 2. The binder resin for toner according to claim 1, wherein the structure of the portion excluding the above is line symmetric or point symmetric.

3. 3. The binder resin for toner according to claim 1, wherein Ar in the formula (1) is a benzene ring.

4. 4. The binder resin for toner according to claim 1, wherein at least one of the crystalline polyester resin and the amorphous polyester resin has an acid value in the range of more than 10.0 and not more than 16.

0.

5. 5. A toner for developing electrostatic images, comprising the binder resin for toners according to claim 1.

6. 6. An electrostatic image developer comprising the toner for developing electrostatic images according to claim 5 and a carrier.

7. A method for producing a binder resin for toner, comprising reacting reactive raw materials including a crystalline polyester resin having an acid value in the range of 4.0 to 16.0, an amorphous polyester resin having an acid value in the range of 4.0 to 16.0, and an aromatic tetracarboxylic acid derivative.

8. 8. The method for producing a binder resin for toner according to claim 7, wherein the aromatic tetracarboxylic acid derivative is an aromatic tetracarboxylic acid derivative in which all four carboxyl groups are directly substituted on an aromatic ring.

9. 9. The method for producing a binder resin for toner according to claim 7, wherein the reaction is carried out in the absence of a solvent.

Citation Information

Patent Citations

  • Toner for electrostatic charge image development, developer for electrostatic charge image development, image forming method, and image forming apparatus

    JP2011197505A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, developer cartridge, process cartridge, image forming apparatus, image forming method, and binder resin for toner for electrostatic charge image development and production method of binder resin

    JP2014092642A

  • Toner for electrostatic charge image development

    JP2017116757A